Melatonin and cardioprotection against ischaemia/reperfusion injury: What's new? A review. Issue 1 (14th April 2018) - Lochner, Amanda; Marais, Erna; Huisamen, Barbara
Abstract: Melatonin is a pleiotropic hormone with several functions. It binds to specific receptors and to a number of cytosolic proteins, activating a vast array of signalling pathways. Its potential to protect the heart against ischaemia/reperfusion damage has attracted much attention, particularly in view of its possible clinical applications. This review will focus mainly on the possible signalling pathways involved in melatonin‐induced cardioprotection. In particular, the role of the melatonin receptors and events downstream of receptor activation, for example, the reperfusion injury salvage kinase (RISK), survivor activating factor enhancement (SAFE) and Notch pathways, the sirtuins, nuclear factor E2–related factor 2 (Nrf2) and translocases in the outer membrane (TOM70) will be discussed. Particular attention is given to the role of the mitochondrion in melatonin‐induced cardioprotection. In addition, a brief overview will be given regarding the status quo of the clinical application of melatonin in humans.